Marketing and Technology a Strategic Co-alignment A Case Based Study - Amit Kundu; Ramanuj Majumdar (2018)
"Firms in high Technology markets are growing at twice the reate of the Economy as a whole and have generated significant returns for their shareholders in recent years. Despite the rapid growth and profit earning capability of the market, developed nation charaterized by technology intensive markets it has found that three critical capabilities of the firm namely marketing Research and Development and Operations that influence the performance of the firms. The present research work examines the relative importance attached to different levels of three capability measures in respect of Technological innovation of the firm in the specific sector as a case. The estimation of the relative importance of the attributes such as Marketing R & D Operations and also the relative importance of the different levels of different attributes is done through conjoint analysis."
Keywords: Marketing